Studi evaluatif ketersediaan dan kualitas ruang terbuka hijau di kawasan Kecamatan Jatinegara - Hakim, Hakim; Endangsih, Tri; Rismawandi, Rismawandi (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2026)
The area surrounding Jatinegara Station has transformed into a commercial zone, driving the expansion of surrounding settlements into densely populated areas. This condition limits the availability of amenities and infrastructure, particularly Green Open Space (GOS), as increasing business intensity drives the transformation of GOS into built-up areas. This study aims to assess the current condition of GOS in the Jatinegara Station area and compare it with the standards stipulated in the Minister of Public Works Regulation Number 05/M/PRT/2008. The method used in this study is a quantitative descriptive analysis technique. GOS requirements are determined based on a standard ratio of 30% of total land area, a standard requirement of 20 square meters per person, and a hierarchical method based on oxygen absorption capacity. The analysis stages involve identifying GOS characteristics, followed by assessments of accessibility, shape, and type. Research findings indicate that while GOS needs based on population and oxygen have been met at 20.78% of the total TOD area, this remains below the regulatory standard of 30%, which requires 20% public and 10% private GOS. Therefore, increasing the GOS area through development and management initiatives that emphasize carbon dioxide-absorbing plants is necessary.